PTU-119 Outcomes of viraemic hepatitis c patients in chester: a 10 year district general hospital experience. (22nd June 2015) - On, W; Caldwell, H; Dale, S; Maheswaran, T; Karmo, M
Abstract : Introduction: Poor access to appropriate healthcare services is implicated as one of the shortcomings of the Hepatitis C (HCV) treatment pathway in the UK and Public Health England has recommended improving accessibility to treatment centres as part of a national strategy to improve treatment uptake rates. 1 The Countess of Chester NHS Foundation Trust (COCH) is the main hospital serving a population of approximately 250, 000 people from the town of Chester and surrounding rural areas. COCH does not provide treatment for HCV and patients are referred to the Royal Liverpool University Hospital NHS Trust (RLUH) for anti-viral therapy. We wanted to assess the impact of segregating HCV services between two separate hospitals on the treatment outcomes and follow-up rates. Method: A retrospective analysis from January 2004 to July 2014 was done. 235 patients with positive HCV serology and a quantifiable viral load confirmed on polymerase chain reaction (PCR) testing were identified from the microbiology database at COCH. Data on treatment outcomes was obtained from the hepatology unit at RLUH. Analysis of patients' case notes and clinic letters was done where appropriate. Results: 87% (204/235) of patients were reviewed in a gastroenterology clinic at COCH. 71% (144/204) of patients seen in clinic were referred to RLUH for treatment. Of the 144 patients referred to RLUH, 28% (41/144) successfully completed treatment. The overall percentage of patients lost to follow-ups due to non-attendances (DNA) was 38% (78/204). The flowchart depicts the known outcomes of the 204 patients seen in clinic. Conclusion: Our data illustrates a 10 year experience of the management of HCV in a district general hospital and supports the need to improve access to HCV treatment centres. Localisation of treatment centres would minimise the burden of travel for patients and improve adherence to treatment. Patients with HCV within a hospital catchment area should also have their care centralised to that hospital to prevent loss to follow-ups. This is particularly important to allow surveillance for complications of chronic HCV infections. Disclosure of interest: None Declared. Reference: Public Health England, Hepatitis C in the UK: 2014 report. (https://www.gov.uk/government/uploads/system/uploads/attachment_data/file/337115/HCV_in_the_UK_2014_24_July.pdf )